1996
DOI: 10.1115/1.2787237
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Elasticity: Theory and Applications

Abstract: The author states in the preface to this book that, in the early 1980s, motivated by the upsurge in research on composite materials, he embarked on anisotropic elasticity research "with little background on isotropic elasticity" and "reluctant and apprehensive in venturing into anisotropic elasticity." He need not have worried. The book under review is a masterly account of the fundamental theory of linear anisotropic elasticity and its applications, with emphasis on the two-dimensional theory. The book consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
909
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(927 citation statements)
references
References 0 publications
8
909
1
9
Order By: Relevance
“…where K is a transformation matrix [58]. In 3D, when we rotate the material about the third coordinate vector by an angle ‚, the transformation matrix reduces to…”
Section: Appendix A: Rotation Of Materials Orientation Relative To Thementioning
confidence: 99%
“…where K is a transformation matrix [58]. In 3D, when we rotate the material about the third coordinate vector by an angle ‚, the transformation matrix reduces to…”
Section: Appendix A: Rotation Of Materials Orientation Relative To Thementioning
confidence: 99%
“…Let t 3 be the only non-zero traction component along the x 3 -direction on a boundary L. If s is the arc-length measured along L such that, when facing the direction of increasing s, the material is on the left-hand side, it is readily shown that [18] …”
Section: (B) Complex Variable Formulationmentioning
confidence: 99%
“…For the anti-plane shear deformation of an isotropic elastic material, the two shear stress components σ 31 and σ 32 , out-of-plane displacement w = u 3 and stress function φ can be expressed in terms of a single analytic function f (z) of the complex variable z = x 1 + ix 2 as [18] σ 32 + iσ 31 = μf (z), φ + iμw = μf (z), (2.4) where f (z) = df (z)/dz. Let t 3 be the only non-zero traction component along the x 3 -direction on a boundary L. If s is the arc-length measured along L such that, when facing the direction of increasing s, the material is on the left-hand side, it is readily shown that [18] …”
Section: (B) Complex Variable Formulationmentioning
confidence: 99%
“…Despite the progresses concerning the mathematical formulation of constitutive laws and the evaluation of overall properties of engineering materials ( [29,9,10,48,19,51,34,41,21,45] and many others, especially in the 2D context), the 3D modelling of interaction between initial and damage-induced anisotropies remains a difficult task, even in the context of phenomenological models (see, for example, [26,44,16,5]). In this paper, this coupling is addressed by means of Eshelby-type homogenization techniques.…”
Section: Introductionmentioning
confidence: 99%